2020
DOI: 10.1111/jocn.15219
|View full text |Cite
|
Sign up to set email alerts
|

Delirium point prevalence studies in inpatient settings: A systematic review and meta‐analysis

Abstract: Aims To examine the delirium point prevalence studies conducted in different inpatient settings and to discuss the implication of the findings for delirium screening, assessment, prevention and management. Background Delirium—a common and distressing condition manifesting as an acute decline of attention and cognition—is frequently overlooked, misdiagnosed or treated inappropriately. This neuropsychiatric syndrome manifests as changes in attention, cognition and awareness, with resultant impact on behaviour, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 48 publications
1
27
2
Order By: Relevance
“…Several other studies found delirium to be common in specific settings including nursing homes 10 and after DBS 6 . By comparison, the delirium point-prevalence across different inpatient settings in general (non-parkinsonian) populations ranges from 9-32% 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies found delirium to be common in specific settings including nursing homes 10 and after DBS 6 . By comparison, the delirium point-prevalence across different inpatient settings in general (non-parkinsonian) populations ranges from 9-32% 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Delirium is common in hospitalised older adults, with a recent meta-analysis of 33 studies of medical inpatients finding an overall delirium occurrence of 23% (95% CI 19–26%) [ 2 ]. It is also common in surgical patients, in care homes and palliative care settings [ 3 ]. Delirium is associated with significant adverse outcomes including functional decline and mortality, and patient and carer distress [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“… 12 Such events can lengthen hospitalisation, produce cognitive changes and lessen the ability to perform the ADL, all potentially leading to unplanned nursing home admission. 12 Indeed, hospitalisation causes an increased risk of the onset of acute cognitive decline in the form of delirium, with a prevalence of up to 60% on some surgical wards, 13 often leading to unplanned nursing home admission. 14 Dementia, Parkinson’s disease and its associated risk of falls, and behavioural changes are common reasons for deciding to transfer inpatients from hospital to long-term care.…”
Section: Introductionmentioning
confidence: 99%